2018
DOI: 10.2147/jmdh.s117945
|View full text |Cite|
|
Sign up to set email alerts
|

Successful strategies in implementing a multidisciplinary team working in the care of patients with cancer: an overview and synthesis of the available literature

Abstract: In many health care systems globally, cancer care is driven by multidisciplinary cancer teams (MDTs). A large number of studies in the past few years and across different literature have been performed to better understand how these teams work and how they manage patient care. The aim of our literature review is to synthesize current scientific and clinical understanding on cancer MDTs and their organization; this, in turn, should provide an up-to-date summary of the current knowledge that those planning or le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
311
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 233 publications
(344 citation statements)
references
References 54 publications
7
311
0
4
Order By: Relevance
“…Important aspects of a successful MDTM are communication and leadership, both of which are shown by the specialists within these teams. Having leaders who understand the importance of protected time for meetings and preparation can improve the quality and efficiency of the meetings, allowing more patients to be discussed …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Important aspects of a successful MDTM are communication and leadership, both of which are shown by the specialists within these teams. Having leaders who understand the importance of protected time for meetings and preparation can improve the quality and efficiency of the meetings, allowing more patients to be discussed …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cancer care coordinators improve effectiveness of MDTMs . While their role varies slightly between health centres, it is important to have a key person to ensure communication between the MDTM, the patient and their health service . They ensure a continuum of care for patients from diagnosis to treatment and follow‐up, and can assist with organising MDTMs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations